Risk factors, prognostic potency, and longitudinal variation of anxiety and depression in postoperative glioma patients - Wu, Xiaohua; Wang, Dongdong; Wang, Dan (Frontiers in Surgery, 2023)
Objective: Anxiety and depression are common mental disorders in glioma patients. This study aimed to evaluate the risk factors, prognostic role, and longitudinal changes in anxiety and depression in postoperative glioma patients. Methods: Anxiety and depression were assessed by Hospital Anxiety and Depression Scale at baseline, month (M) 6, M12, M24 and M36 in 270 glioma patients after surgical resection. Furthermore, comprehensive clinic characteristics and treatment-related information were collected. Results: Gender (female vs. male) (P=0.014, odds ratio (OR)=1.974), marital status (single/divorced/widowed vs. married) (P=0.019, OR=2.172), Karnofsky performance status (KPS) score (≤70 vs. >70) (P=0.002, OR=2.556), World Health Organization (WHO) classification (high-grade glioma (HGG) vs. low-grade glioma (LGG)) (P=0.005, OR=2.155), and postoperative complications (yes vs. not) (P=0.001, OR=2.525) were independently related to anxiety occurrence. Marital status (single/divorced/widowed vs. married) (P=0.034, OR=2.026), KPS score (≤70 vs. >70) (P<0.001, OR=3.880), WHO classification (HGG vs. LGG) (P=0.032, OR=1.810), and postoperative complications (yes vs. not) (P=0.001, OR=2.602) were independently related to depression occurrence. Besides, anxiety (P=0.038) and depression (P=0.013) were linked with shorter overall survival (OS), and depression was an independent risk factor for worse OS (P=0.040, hazard ratio=1.596). More importantly, anxiety and depression remained at a high prevalence during a 3-year follow-up. Conclusion: Gender, marital status, KPS score, WHO classification, and postoperative complications are risk factors for anxiety and depression; moreover, anxiety and depression are at high prevalence continuously and correlated with worse survival in postoperative glioma patients.